2019
DOI: 10.3389/fphar.2019.00856
|View full text |Cite
|
Sign up to set email alerts
|

Amentoflavone Affects Epileptogenesis and Exerts Neuroprotective Effects by Inhibiting NLRP3 Inflammasome

Abstract: Brain inflammation is one of the main causes of epileptogenesis, a chronic process triggered by various insults, including genetic or acquired factors that enhance susceptibility to seizures. Amentoflavone, a naturally occurring biflavonoid compound that has anti-inflammatory effects, exerts neuroprotective effects against nervous system diseases. In the present study, we aimed to investigate the effects of amentoflavone on epilepsy in vivo and in vitro and elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 50 publications
3
65
0
3
Order By: Relevance
“…The assembly of the NLRP3 inflammasome results in the conversion of procaspase-1 from its pro form to its active form, which then processes the cleavage of several substrates, such as pro-IL-1β and pro-IL-18, in the mature cytokines IL-1β and IL-18 [108]; this process can aggravate inflammation. In addition, numerous studies have implicated neuroinflammation as the cause, and result, of epilepsy [109,110].…”
Section: Connexins-based Hemichannels/channels and Neuroinflammationmentioning
confidence: 99%
“…The assembly of the NLRP3 inflammasome results in the conversion of procaspase-1 from its pro form to its active form, which then processes the cleavage of several substrates, such as pro-IL-1β and pro-IL-18, in the mature cytokines IL-1β and IL-18 [108]; this process can aggravate inflammation. In addition, numerous studies have implicated neuroinflammation as the cause, and result, of epilepsy [109,110].…”
Section: Connexins-based Hemichannels/channels and Neuroinflammationmentioning
confidence: 99%
“…The flavonoids in the fruit extract of A. bunius such as coumarin, genistin, amentoflavone and luteolin 7-galactoside have already been proved to have multiple biological activities [15,16,17]. Amentoflavone is a naturally occurring biflavonoid compound abundant in Selaginella tamariscina, with antiinflammatory [18], anti-oxidative [19], anti-microbial [20], anti-apoptotic [21], anti-radiation [22], antitumor [12], neuroprotective [23,24] and cyano-bacterial killing effects [25]. Previously, the authors confirmed the antiproliferative effect of the ethanolic extract of leaves of Antidesma montanum on the MDA-MB-231 cells and found that amentoflavone was present in this extract [26].…”
Section: Discussionmentioning
confidence: 99%
“…Stage 0: normal behavior; stage 1: immobility; stage 2: facial and neck jerks; stage 3: tail extension; stage 4: chronic seizure (sitting); stage 5: generalized chronic, tonic-clonic seizure (lying on belly); stage 6: generalized chronic, tonic-clonic seizure (lying on side); stage 7: full tonic extension; and stage 8: death [35][36][37]. Kindling paradigm: mice were treated with a subconvulsive dose of PTZ (35 mg/kg) every other day, observed for the next 15 min and scored for seizure severity after each PTZ injection based on a modified Racine scale [38][39][40]. Stage 0: normal behavior; stage 1: immobilization or facial myoclonus; stage 2: head nodding; stage 3: forelimb clonus or short myoclonic jerks; stage 4: rearing generalized chronic seizure; stage 5: generalized tonic-clonic seizures and falling with loss of posture; and stage 6: death.…”
Section: Ptz Dosing Paradigmsmentioning
confidence: 99%